Authentic research experience through mock grant application roleplay - Tan, Hock Siew; Lim, Caryn (Frontiers in Education, 2023)
Many universities resort to online teaching due to the COVID-19 pandemic. It is a challenging endeavour, especially in Biology courses that require lab access. Mock grant application roleplay is one alternative to lab-based activities. Although using mock grant applications as an assessment tool is not new, there have been few studies on students' opinions. This is the first time that it has been used in place of lab-based exercises and in conjunction with virtual lab modules. Students are engaged in three aspects: (i) targeted literature review, (ii) research proposal writing and (iii) 5-min project pitching. The design of this module is flexible, and other lab-based courses can adopt it. This module encourages undergraduate students to explore the lab techniques and concisely present their research proposals. Compared to the previous semester before COVID-19, the number of students that achieved the "Distinction" grade or higher increased by 6.3%, while the failures decreased by 3.2%. A survey among students who took this unit reported that student satisfaction with this unit has improved by 11.1%. This improvement could be attributed to this mock grant activity because the format and difficulty level of the student assessments had remained constant. Qualitative analysis conducted via focus group interviews indicated that students agreed that the mock grant proposal assessment was useful in preparing them for future careers and was relevant to the course learning outcomes. In conclusion, this roleplay module can fulfil the learning objectives of this course while providing an authentic research experience without lab-based activities.